Results of Educational Quality Accreditation and Major Problems of 17 Private Higher Education Instituitions - Thi Hoa, Dao; Van, Dang Ung; Xuan, Nguyen Thi Le; Thuong, Nguyen Thi (VNU Journal of Science: Education Research; Vol 35 No 3DO - 10.25073/2588-1159/vnuer.4252, 2019)
This paper not only outlines the results of external assessment and the accreditation of educational quality of 17 non-state universities according to the Consolidated Document No. 06/2014 / VBHN-BGD  DT, implemented by 4 Educational Quality Centers and published the Resolution on social networks, but also proves the foundation of that accreditation’s results. With a dataset of 115 samples, we compared with the results of the quality accreditation of 100 public universities and 17 non-public universities proposing the main reasons that the criteria have not been achieved in the non-public universities and some recommendations. Due to the limited framework of the article and the fact that up to now only 17 non-public universities have been assessed base on the old standards (including 10 standards and 61 criteria), we only focus on presenting criteria that more than 20% of non-state institutions have not met the requirements. (among those 17 non-state universities).